The Role of the Village Head in the Covid-19 Pandemic Period (A Study in the District of West Bangkala, Jeneponto Regency) - Try Gustaf Said; Rismawati Rismawati; Ayu Fauziah Suryadi (Universitas of Muhammadiyah Makassar, 2022)
This study aims to find out and then describe the role played by the Village Head in dealing with Covid-19 as well as what obstacles he faced and what efforts were made by the Village Head in West Bangkala District, Jeneponto Regency, in this case, Beroanging village, Barana village, and Bulu village. Jaya. The type of research used is descriptive qualitative. Data collection techniques include observation, interviews, and documentation. And as for the data analysis techniques, namely data collection, data reduction, data presentation, and conclusion drawing. This study's results indicate that the village head's role during the pandemic has been perfect because the village head has taken precautions related to Covid-19, such as establishing a post at every border entering and leaving the village, conducting socialization, distributing masks, making hand washing stations at several points, and providing BLT assistance from village funds. And spraying disinfectants. The obstacle faced was that village infrastructure development was hampered because funds were diverted to cope with the impact of COVID-19 and limited community activities, so it also had an impact on the community's economy. The efforts offered by the village head, such as continuing to socialize and educate the public about the importance of complying with health protocols and conducting surveillance in places that have the potential to cause crowds, such as in markets.